Best practices in Scala programming : guidelines for ensuring a professional Scala code base - Backfield, Joshua (O'Reilly, 2016)
"Anyone starting a project in Scala, expanding a Scala project, or looking to establish coding standards as a means for helping junior Scala programmers come up to speed, will value this overview of Scala best practices by Scala expert Joshua Backfield. Backfield's extensive experience in both object-oriented programming and functional programming make him a Scala authority. He has ported multiple native C applications to Scala, introduced many coworkers to Scala, and taught them the underlying functional programming concepts. He uses that experience to offer a set of Scala guidelines that should make your Scala code base as great as it can be. Review and master the coding standards used by expert Scala programmers; Learn methods for ensuring that junior level programmers adhere to coding standards; Understand the norms for var and val usages and functions as objects; Review standards for immutable vs. mutable data structures and for pattern matching; Master axioms in OOP for use cases, instance methods, and mixing vs. deep inheritance; Learn standards for advanced features like avoiding postfix notation and dynamic typing; Understand best practices for syntax, concurrency, and self-documenting code."--Resource description page.